Climate change and the urgency to transform food systems - Zurek, M; Hebinck, A; Selomane, O (American Association for the Advancement of Science, 2022)
Without rapid changes to agriculture and food systems, the goals of the 2015 Paris Agreement on climate change will not be met. Food systems are one of the most important contributors to greenhouse gas (GHG) emissions, but they also need to be adapted to cope with climate change impacts. Although many options exist to reduce GHG emissions in the food system, efforts to develop implementable transformation pathways are hampered by a combination of structural challenges such as fragmented decision-making, vested interests, and power imbalances in the climate policy and food communities, all of which are compounded by a lack of joint vision. New processes and governance arrangements are urgently needed for dealing with potential trade-offs among mitigation options and their food security implications.